ISLAMIC MICROFINANCE: AN ADOPTION OF EQUITY FINANCING MODEL IN MALAYSIA - MOHD ABD KHAR, SITI HAJAR (2020)
Microfinance is one among the crucial finance sectors in Malaysia. The micro, small and medium businesses rely on microfinance for finance support. These businesses influence the economy’s growth which indirectly made microfinance to be significant as other finance sector. This industry providing services to the unbankable group. Yet, the studies on Islamic microfinance are less established particularly on the finding of what products could be offered to the poor. The current phenomena states that most of microfinance institutions are only providing debt-based financing as their finance products to the poor community. There is a need to identify other products of equity based financing as an alternative financing for the poor. Thus the microfinance sector will be more helpful to the poor and micro entrepreneur by extending the product list. The objectives of this paper are to explore the perception of the Micro-entrepreneurs (ME) and the Experts of Islamic microfinance toward the adoption of equity financing models in Malaysia. The quantitative method is used where questionnaires are distributed to 611 micro-entrepreneurs in order to gauge their perception regarding equity financing. While qualitative interview is used to explore the perception of four experts toward the subject discussed. The integrated result shows that the respondents of both questionnaire and interview have positive perception toward this equity models.